CHARACTERISTICS OF PATIENTS WITH MEASLES ADMITTED TO ALLIED HOSPITAL RAWALPINDI - Sultana, Abida; Sabir, Syed Arshad; Awan, Amna (Journal of Ayub Medical College Abbottabad, 2015)
Background: Measles, a virus borne droplet infection, is one of the leading causes of death among young children worldwide despite presence of a safe and cost-effective vaccine. Objective of our study was to identify the characteristics of measles patients admitted to Allied Hospitals, Rawalpindi. Methods: This cross-sectional study was conducted amongst patients admitted with measles in paediatric units of Rawalpindi Medical College Allied Hospitals, Rawalpindi. A standard pro forma was used to collect data from the respondents. Results: A total of 55 patients (mean age-29.36 months) with measles were included in the study. 65.5% children were vaccinated while 34.5% were not vaccinated. Among those vaccinated 14 were male. Out of the vaccinated children 52.6% were residents of middle class areas, 31.6% lower middle class area, 10.5% upper middle class areas and 5.3% rural areas. In 55.0% of patients who were vaccinated with at least one dose of measles at nine month of age the estimated calendar months of vaccination was March to April while in 30% the overall climatic period of vaccination was of summer (May to September). Twenty one study subjects were exposed to a case of measles in the family and thirty five out of all developed at least one known complication of the disease. Pneumonia was the most common complication reported in patients (63.6%) followed by diarrhoea (27.3%). Conclusion: Majority of the patients suffering from measles were not vaccinated and the most common reason for failure to immunize children was lack of awareness. Educated and well off fathers were more likely to get their children immunized. The vaccinated children who developed measles majority were vaccinated during months of March, April and May. Keywords: Measles, immunization, outbreaks.